MOneyQU: A Gamified Android Based Personal Finance Recording Application - Juwono, Firdayanti; Gunawan, Dennis (Pandawan Sejahtera Indonesia, 2021)
Financial management is a knowledge which is not only important to learn but also important to be applied in life of each individual. In recognizing financial conditions, motivation can be one of the factors which influence it. Gamification can be one way to increase the motivation and must be adapted to the characteristics of the users. Focusing on goals, engagement, and intrinsic motivation, Marczewski Gamification Framework maps several user types based on the game elements and mechanics. This study aims to design and build a mobile-based personal financial recording application with gamification methods and find out the level of behavioral intention to use and immersion implementing the Marczewski Gamification Framework. Testing has been carried out by students, employees, housewives, entrepreneurs, and managers to prove that gamification can motivate users to recognize the condition of personal finances well. Based on the evaluation result using the Hedonic Motivation System Adoption Model, 82.73% strongly agree that the application can increase reuse (behavioral intention to use) in the future and 66.56% agree that the application can increase the feeling of users to be carried away by the situation (immersion) in the application.